Financial Ratios and Financial Distress in Consumer Cyclicals Companies: Evidence from the COVID-19 and Economic Recovery Period - Abimanyu Abimanyu; Lina Nur Hidayati (Fairness, 2026)
Objective: This study aims to analyze the effect of financial ratios, namely profitability, liquidity, leverage, and activity ratios, on financial distress in consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period.Research Design & Methods: This study employed a quantitative approach with a causal associative research design. The population consisted of consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2022. Secondary data were collected from audited annual financial statements and analyzed using ordinal logistic regression with IBM SPSS Statistics.Findings: The results indicate that profitability and liquidity ratios have a negative effect on financial distress, implying that companies with higher profitability and stronger liquidity are less likely to experience financial difficulties. In contrast, the leverage ratio has a positive effect on financial distress, indicating that greater reliance on debt increases the risk of financial distress. Meanwhile, the activity ratio does not significantly affect financial distress. Furthermore, the coefficient of determination shows that financial ratios simultaneously explain 51% of the variation in financial distress, while the remaining 49% is influenced by other factors outside the model.Implications: The findings highlight the importance of maintaining profitability, liquidity, and prudent debt management as preventive measures against financial distress, particularly in the consumer cyclicals sector, which is highly sensitive to economic fluctuations and changes in consumer purchasing power.Contribution & Value Added: This study contributes to the financial distress literature by providing empirical evidence on the role of financial ratios as early warning indicators of financial distress in the consumer cyclicals sector during a period characterized by pandemic-related disruption and economic recovery. The findings offer practical insights for managers, investors, creditors, and regulators in assessing corporate financial health and mitigating financial distress risk under continuing economic uncertainty.